Demographic and psychosocial correlates of quality of life in the elderly from a cross-cultural perspective - Dragomirecká, Eva; Bartonová, Jitka; Eisemann, Martin; Kalfoss, Mary; Kilian, Reinhold; Martiny, Klaus; von Steinbüchel, Nicole; Schmidt, Silke (Clinical psychology & psychotherapy, 2008)
We compared the quality of life (QOL) of older adults in a post-communist country (the Czech Republic) with those living in traditional western democracies. The sample comprised 1981 respondents aged 60+ (from 60 to 99). The subjective QOL was measured using the WHOQOL-BREF and the add-on module for older adults, the WHOQOL-OLD. The findings showed higher score of depressive symptoms measured by the GDS scale and lower QOL in Czech sample as compared to other centres. Analyses of factors related to QOL of older adults showed similar patterns for the Czech sample and other centres with depression emerging as the strongest determinant of reduced QOL Findings also underline that subjective quality of life measurement reflects cross-country differences in accordance with objective indicators of national prosperity.
Keywords: Socioeconomic Factors; Psychometrics; Cross-Sectional Studies; Cross-Cultural Comparison; Male; kvalita života; Aging; Quality of Life; ukazatele zdravotního stavu; Česká republika; Europe; socioekonomické faktory; Aged; mužské pohlaví; senioři; reprodukovatelnost výsledků; průzkumy a dotazníky; depresivní poruchy; Reproducibility of Results; Social Change; Czech Republic; Evropa; Social Environment; senioři nad 80 let; lidé; ženské pohlaví; psychometrie; Humans; průřezové studie; stárnutí; sociální změna; Aged, 80 and over; Depressive Disorder; sociální prostředí; Female; Health Status Indicators; Surveys and Questionnaires; srovnání kultur; lidé středního věku; Middle Aged